A room temperature stable non-crystallized twisted nematic liquid crystal dimer material and its application
By mixing liquid crystal dimer materials such as CBnCB, CBnOCB, CBOnOCB, etc. in specific proportions, and using intermolecular interactions and entanglement, the problem of existing twisted and curved nematic liquid crystal materials is solved, and the stable and crystalless NTB phase state is achieved at room temperature is achieved, and the stability of the material is significantly improved.
Patent Information
- Application Number
- CN202310908652.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-07-24
AI Technical Summary
The existing twisted and curved nematic liquid crystal materials are unstable at room temperature and are prone to crystallization. They are difficult to design molecularly, have long chemical synthesis cycles, and are difficult to purify, so they cannot maintain the NTB phase state for a long time.
By mixing liquid crystal dimer materials such as CBnCB, CBnOCB, CBOnOCB, etc. in specific proportions, using the interaction between molecules and the entanglement of molecular chains, the supercooling ability of the material is significantly enhanced and a stable NTB phase state is achieved at room temperature.
A stable, reliable, crystalless NTB phase state at room temperature was achieved. The sample maintained a wide temperature range of NTB phase state region and did not have any crystallization for at least 300 days, significantly improving the stability of the material.
Smart Images

Figure CN117210227B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid crystal materials, and in particular relates to a room temperature stable non-crystallized twisted bend nematic phase liquid crystal dimer material and application thereof. Background Art
[0002] Twisted bend nematic liquid crystal (N TB ) is a new type of nematic liquid crystal material discovered in the past decade. It is composed of bent molecules and has a nanoscale periodic spiral structure. It is a photonic material with wide application potential. TB Liquid crystal materials have the advantages of fast response speed, wide viewing angle, low voltage drive, and low power consumption. Therefore, they have broad application prospects in liquid crystal display, optical communication, laser modulators, biosensors and other fields.
[0003] N TB The study of liquid crystal materials began in 2010, and this phase was discovered in various bent liquid crystal dimer compounds containing flexible methylene spacers, such as CB7CB. TB Liquid crystal materials have received more and more attention, involving the synthesis, property characterization, theoretical simulation, and application of materials. TB The temperature range of the liquid crystal phase is closely related to its chemical structure and usually only exists at higher temperatures and in a narrow temperature range, which greatly limits its implementation in device manufacturing. Ideally, it needs to be stable at room temperature.
[0004] At present, there are some schemes that have the potential to reduce the N by designing specific molecular structures, such as introducing S bonds into the molecular structure and introducing pyrene-based functional groups. TB The temperature range of the phase, or the rapid cooling process to form glassy N TB However, although the above methods can obtain N at low temperature or room temperature TB However, this state is extremely unstable and will crystallize after being stored for a few hours, so it is still not practically applicable.
[0005] Through specific molecular structure design, such as functional modification on the structure of liquid crystal dimer, introduction of some specific functional groups such as sulfur bond, pyrene, changing the symmetry of liquid crystal dimer molecular structure, etc., to optimize N TB The temperature range of the phase can obtain N in a larger temperature range. TB phase, and even room temperature N TBHowever, the above molecular design scheme faces the following three main challenges: 1) Although the current materials can reach low temperature or room temperature, the above material system is extremely unstable. After the sample is stored for a few hours or a few days, it will crystallize; 2) Molecular design is difficult, the chemical synthesis cycle is long, and the purification is difficult; 3) The uncertainty of molecular design is large, and it is impossible or unsatisfactory to obtain N TB phase, even the synthesized molecules cannot form N TB Phase.
[0006] Through some specific processes such as rapid liquid nitrogen refrigeration or specific liquid crystal dimer molecular design, glassy N TB Phase. Depending on the molecular structure, the glass transition temperature of liquid crystal dimers can be at an extremely low temperature close to 0°C or above room temperature. TB The phase state is also extremely unstable, which manifests itself in two aspects: on the one hand, it cannot respond normally to an external electric field, and once an electric field is applied to it or a large temperature change occurs, this glassy N TB There will be a structural collapse, from N TB On the other hand, this room temperature N TB The phase state is still not stable for a long period of time and crystallization will occur after a few days of storage. Summary of the invention
[0007] The purpose of the present invention is to provide a room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material.
[0008] Another object of the present invention is to provide an application of the room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material in the preparation of display panels and display devices.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] The first aspect of the present invention provides a room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material, selected from at least one of CBnCB, CBnOCB, and CBOnOCB, where n is selected from a positive integer from 3 to 15 (such as 3, 4, 5, 6, 7, 8, 9, 10, 11, 12);
[0011] The structure of CBnCB is as follows:
[0012]
[0013] The structure of CBnOCB is as follows:
[0014]
[0015] The structure of CBOnOCB is as follows:
[0016]
[0017] Preferably, the room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 30% to 75%, CB9CB 15% to 45%, CB11CB 5% to 25%;
[0018] The structure of CB7CB is as follows:
[0019]
[0020] The structure of CB9CB is as follows:
[0021]
[0022] The structure of CB11CB is as follows:
[0023]
[0024] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by mass: 40% to 60% of CB7CB, 20% to 40% of CB9CB, and 10% to 20% of CB11CB.
[0025] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by mass: 60% of CB7CB, 20% of CB9CB and 20% of CB11CB.
[0026] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: 40% of CB7CB, 40% of CB9CB, and 20% of CB11CB.
[0027] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 50%, CB9CB 35%, CB11CB 15%.
[0028] The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 55%, CB9CB 30%, CB11CB 15%.
[0029] The second aspect of the present invention provides an application of the room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material in the preparation of a display panel and a display device.
[0030] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:
[0031] The room temperature stable non-crystallized twisted bend nematic liquid crystal material provided by the present invention has simple monomer components and a simple preparation process. By mixing a plurality of liquid crystal dimer materials with different molecular bending degrees and central flexibility degrees in a specific ratio, the supercooling ability of the material system is significantly enhanced by means of the interaction between molecules and the entanglement of molecular chains, thereby achieving stable, reliable, non-crystallized N-terminal phase at room temperature. TB phase, the sample maintains N over a wide temperature range TB phase region, and there is no crystallization for at least 300 days. TB In-depth research on phase states is of great significance to the development of modern photonics.
[0032] The room temperature stable non-crystallized twisted bend nematic liquid crystal material provided by the present invention can effectively improve the overall stability of the material system according to different dimer component ratios; the room temperature stable non-crystallized twisted bend nematic liquid crystal material has a wide temperature range of N TB Phase, from room temperature to nearly 100°C.
[0033] The room temperature stable non-crystallized twisted nematic liquid crystal material provided by the present invention can meet the long-term storage requirements. TB Even when the phase is stored at room temperature for more than 300 days, no crystallization phenomenon is observed. The material system exhibits excellent stability, far exceeding other material systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic diagram of the molecular structure of CB7CB, CB9CB, and CB11CB and their polarized microtexture and phase state during the cooling process.
[0035] Figure 2 It is a schematic diagram of the time when crystallization occurs after sample S4, sample S5, sample S6, sample S7, and sample S8 are stored at room temperature.
[0036] Figure 3 It is a schematic diagram of XRD analysis of sample S4, sample S5, sample S6, sample S7 and sample S8 after storage at room temperature.
[0037] Figure 4 It is a schematic diagram of differential scanning calorimetry (DSC) data of samples S4, S5, S6, S7 and S8 when the temperature is lowered from 130°C at a rate of 5°C / min. DETAILED DESCRIPTION
[0038] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0039] For the preparation of CBnCB, CBnOCB and CBOnOCB in the embodiments of the present invention, refer to the literature: Liq.Cryst.2017,44,127-146.
[0040] The reagents used in the embodiments of the present invention are as follows:
[0041] 1,5-Bis-4-(4'-cyanobiphenyl)pentane—CB5CB Molecular formula:
[0042]
[0043] 1,7-Bis-4-(4'-cyanobiphenyl)heptane—CB7CB Molecular formula:
[0044]
[0045] 1,9-Bis-4-(4'-cyanobiphenyl)nonane—CB9CB Molecular formula:
[0046]
[0047] 1,11-Bis-4-(4'-cyanobiphenyl)undecane—CB11CB Molecular formula:
[0048]
[0049] 1-(4-cyanobiphenyl-4'-oxy)-4-(4-cyanobiphenyl-4'-yl)hexane—CB4OCB Molecular formula:
[0050]
[0051] 1-(4-cyanobiphenyl-4'-oxy)-6-(4-cyanobiphenyl-4'-yl)hexane—CB6OCB Molecular formula:
[0052]
[0053] 1,3-Bis(4-cyanobiphenyl-4'-oxy)alkane-CBO3OCB Molecular formula:
[0054]
[0055] The synthetic route of CBnCB material is as follows:
[0056] Adipoyl chloride and 4-bromobiphenyl were added dropwise to a suspension of aluminum chloride / dichloromethane and stirred, the reaction mixture was added to water and shaken with dichloromethane. The remaining aqueous suspension was filtered, the solid was thoroughly washed with water and recrystallized from toluene. Triethylsilane was added dropwise to α,ω-bis(4'-bromobiphenyl-4-yl)butane and stirred in a trifluoroacetic acid and dichloromethane solution. The reaction mixture was allowed to reach room temperature and stirred for 48 hours, then the white solid was filtered off, washed with water and recrystallized from toluene. A mixture of α,ω-bis(4'-bromobiphenyl-4-yl)hexane, cuprous cyanide, and dry N-methylpyrrolidone was stirred at 200°C for 4 hours, then cooled to 80°C, and ferric chloride and hydrochloric acid were added. After stirring for another 30 minutes, the mixture was allowed to cool overnight, water was added, and it was shaken with dichloromethane. The organic layer was washed with water, dried over CaCl2 and the solvent was removed, and finally recrystallized from toluene.
[0057]
[0058] Example 1
[0059] A room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material is prepared from the following components in percentage by weight: 60% of CB7CB, 20% of CB9CB, and 20% of CB11CB. The material is named as sample S7.
[0060] During the test, each substance is weighed according to the above ratio, and stirred evenly for 2 hours at a temperature of 130° C. to make it evenly mixed before the test. The following examples and comparative examples are all carried out according to this method.
[0061] Example 2
[0062] A room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 40%, CB9CB 40%, CB11CB 20%, and the material is named sample S8.
[0063] Example 3
[0064] A room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material is prepared from the following components in percentage by weight: CB7CB 50%, CB9CB 35%, CB11CB 15%, and the material is named as sample S9.
[0065] Example 4
[0066] A room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 55%, CB9CB 30%, CB11CB 15%, and the material is named sample S10.
[0067] Comparative Example 1
[0068] CB7CB was used as a single component and the material was named sample S1.
[0069] Comparative Example 2
[0070] CB9CB was used as a single component and the material was named sample S2.
[0071] Comparative Example 3
[0072] CB11CB was used as a single component and the material was named sample S3.
[0073] Comparative Example 4
[0074] A liquid crystal material is made of the following components in percentage by weight: CB7CB 60%, CB9CB 40%, and the material is named sample S4.
[0075] Comparative Example 5
[0076] A liquid crystal material is made of the following components in percentage by weight: CB7CB 60%, CB11CB 40%, and the material is named sample S5.
[0077] Comparative Example 6
[0078] A liquid crystal material is made of the following components in percentage by weight: CB9CB 60%, CB11CB 40%, and the material is named sample S6.
[0079] The three groups of samples S1, S2, and S3 were heated to 130°C to melt them into liquid state. At this temperature, they were poured into a liquid crystal cell (size: 15*18mm) with surface parallel alignment. 2 , thickness 12μm), placed in a precision temperature-controlled hot stage, slowly cooled at a rate of 3℃ / min, and observed its phase transition. The results are as follows Figure 1 As shown, Figure 1 The molecular structure of CB7CB, CB9CB, and CB11CB and their polarized microtexture and phase state during the cooling process are shown in Figure 2. For sample S1CB7CB, as the temperature decreases, it changes from liquid to nematic phase (N phase) at 117°C, and from N phase to twisted nematic phase (N phase) at 104°C. TB ). In the N phase, the polarization texture appears as a uniform color. TB In the phase, a rope-like polarized texture is presented. TB The phase state can be maintained until the room temperature is 25℃, which is supercooling. TBVery unstable, crystallization occurs in about 2 hours. Similar results also appear in samples S2CB9CB and S3CB11CB. Among them, sample S2 crystallizes at 40℃, while sample S3 crystallizes directly at 80℃. Therefore, the above three samples can show that for general liquid crystal dimer materials, it is usually impossible to obtain room temperature N TB Phase, or its N TB The phase state is extremely unstable and crystallization occurs easily.
[0080] The three liquid crystal dimer materials CB7CB, CB9CB, and CB11CB were weighed according to the proportions of samples S4, S5, S6, S7, S8, S9, and S10 and placed in a sample bottle for mixing. A magnetic stirrer was added to the sample bottle to stir the sample evenly at 130°C for 2 hours to make it evenly mixed. At this temperature, it was poured into a liquid crystal box with a surface parallel alignment (size 15*18mm 2 , thickness 12μm), placed in a precision temperature-controlled hot stage, slowly cooled at a rate of 3℃ / min, and observed its phase transition. The phase transition of samples S4, S5, S6, S7, and S8 is very similar to that of samples S1, S2, and S3. They transform from liquid to conventional N phase at about 120℃, and from N phase to N at about 105℃. TB Phase. N of sample S4, sample S5, sample S6, sample S7, and sample S8 TB Both phases can be supercooled to room temperature 25°C.
[0081] The N content of the material was characterized by polarizing microscope (POM) and X-ray diffraction (XRD). TB Temperature range of phase state and room temperature stability. Samples S4, S5, S6, S7 and S8 were stored at room temperature and their stability and crystallization were monitored by POM. TB The phase state can be confirmed by the images measured by polarizing microscope. Figure 2 As shown, Figure 2 This is a schematic diagram of the time when sample S4, sample S5, sample S6, sample S7, and sample S8 crystallize after being stored at room temperature. As can be seen from the figure, Figure 2 The first picture on the left shows the initial state of samples S4-S8 at room temperature. The molecules are arranged in a rope-like manner. This picture proves that N TB In the initial state, each sample is supercooled N at room temperature 25℃. TBPhase, POM shows a rope-like texture. However, the crystallization stability of the above samples is closely related to the material composition. For example, sample S4 crystallized on the 5th day; sample S5 crystallized on the 17th day; sample S6 was very unstable and crystallized on the first day. Samples S7 and S8 showed amazing stability. Even after being stored for more than 300 days, there was no crystallization, and their polarized microscopy images remained the same as the initial state, proving their extremely strong stability.
[0082] In order to further confirm the stability of the above material system, the present invention also used XRD method to analyze the above samples S4, S5, S6, S7 and S8. The results are as follows Figure 3 As shown, Figure 3 Figure 1 is a schematic diagram of XRD analysis of samples S4, S5, S6, S7, and S8 after storage at room temperature. First, XRD analysis was performed on the samples after 10 days of storage. At this time, samples S4 and S6 had crystallized, so their XRD results showed multiple peaks, indicating the structure of the crystal; while sample S5 was not crystallized at this time and was in a supercooled state. TB Phase state, therefore, no crystallization peak was observed in the XRD results. Samples S7 and S8 have the characteristics of being stable and non-crystallized. After being stored for 180 days, XRD analysis was performed on them. It can be seen that no crystallization peak appeared, proving that the samples are still in the supercooled N TB Phase.
[0083] The DSC data results are as follows: Figure 4 As shown, Figure 4 This is a schematic diagram of the differential scanning calorimeter analysis (DSC) data of samples S4, S5, S6, S7, and S8 when they were cooled from 130°C at a rate of 5°C / min. From right to left in the figure, these material systems have a peak at around 120 degrees and around 100 degrees respectively. The appearance of peaks on the curve proves that the material has undergone a phase change. Therefore, in the process of cooling from high temperature, these samples change from liquid (Iso) to nematic phase (N) at about 120°C and to twisted nematic phase (N) at about 100°C. TB ). When the temperature is lowered to room temperature, no other peaks are found, which proves that below about 100°C, the material is in N TB Phase.
[0084] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.
Claims
1. A room temperature stable non-crystallized twisted nematic liquid crystal dimer material, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 30% to 75%, CB9CB 15% to 45%, CB11CB 5% to 25%; The structure of CB7CB is as follows: The structure of CB9CB is as follows: The structure of CB11CB is as follows:
2. The room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to claim 1, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by mass: 40% to 60% of CB7CB, 20% to 40% of CB9CB, and 10% to 20% of CB11CB.
3. The room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to claim 1, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by mass: 60% of CB7CB, 20% of CB9CB and 20% of CB11CB.
4. The room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to claim 1, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: 40% of CB7CB, 40% of CB9CB, and 20% of CB11CB.
5. The room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to claim 1, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 50%, CB9CB 35%, CB11CB 15%.
6. The room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to claim 1, characterized in that: The room temperature stable non-crystallized twisted nematic phase liquid crystal dimer material is made of the following components in percentage by weight: CB7CB 55%, CB9CB 30%, CB11CB 15%.
7. Use of the room temperature stable non-crystallized twisted bend nematic liquid crystal dimer material according to any one of claims 1 to 6 in the preparation of display panels and display devices.
Citation Information
Patent Citations
Field induced and controlled heliconical structure of cholesteric liquid crystal
US20160252755A1